Senyawa Fitokimia dan Aktivitas Antibakteri Ekstrak Etanol Buah Lerak (Sapindus rarak) terhadap Tiga Bakteri Penyebab Infeksi Nosokomial - Retno Widowati; Muhammad Firdaus Ramdani; Sri Handayani (FORIKES, 2022)
Nosocomial infection is one of the microorganism infections in the hospital environment which is very detrimental to the world of health. One of the potential natural ingredients that can be an alternative to antibacterial compounds in preventing nosocomial infections is lerak fruit (Sapindus rarak). This study aims to determine the active phytochemical compounds and antibacterial activity of the ethanolic extract of lerak fruit in inhibiting the growth of bacteria that cause nosocomial infections. The method used was a factorial completely randomized design. Types of phytochemical tests used were tests for alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, steroids, glycosides. The antibacterial activity test was carried out using the tube diffusion method with several variations in concentration; 25%, 50%, 75%, and 100%. The types of bacteria tested were Staphylococcus aureus (ATCC 6539), Staphylococcus epidermidis (ATCC 12228), and Pseudomonas aeruginosa (ATCC 9027). Data analysis was performed using One-way ANOVA then followed by post-hoc test to determine the concentration that gave the most significant difference in effect using Tukey's test. The results of the analysis showed that the lerak fruit had eight active substances as tested. The antibacterial inhibition zone showed the presence of a radical zone and an irradical zone. The ethanolic extract of lerak fruit has antibacterial properties that can inhibit the growth of S. epidermidis, S. aureus, and P. aeruginosa. The nature of the ethanolic extract of the lerak fruit against the test bacteria was bacteriostatic.Keywords: antibacterial; phytochemicals; nosocomial infections; lerak fruit ABSTRAK Infeksi nosokomial merupakan salah satu infeksi mikroorganisme di lingkungan rumah sakit yang sangat merugikan dunia kesehatan. Salah satu potensi bahan alam yang dapat menjadi alternatif senyawa antibakteri dalam mencegah infeksi nosokomial adalah buah lerak (Sapindus rarak). Penelitian ini bertujuan untuk mengetahui senyawa aktif fitokimia dan aktivitas antibakteri ekstrak etanol buah lerak dalam menghambat pertumbuhan bakteri penyebab infeksi nosokomial. Metode yang digunakan adalah rancangan acak lengkap faktorial. Jenis uji fitokimia yang digunakan adalah uji untuk alkaloid, saponin, tanin, fenolik, flavonoid, triterpenoid, steroid, glikosida. Uji aktivitas antibakteri dilakukan dengan menggunakan menggunakan metode difusi sumuran dengan beberapa variasi konsentrasi; 25%, 50%, 75%, dan 100%. Jenis bakteri yang diuji adalah Staphylococcus aureus (ATCC 6539), Staphylococcus epidermidis (ATCC 12228), dan Pseudomonas aeruginosa (ATCC 9027). Analisis data dilakukan menggunakan One-way ANOVA kemudian dilanjutkan dengan uji post-hoc untuk mengetahui konsentrasi yang memberikan perbedaan efek paling bermakna menggunakan uji Tukey. Hasil analisis menunjukkan buah lerak memiliki delapan zat aktif sesuai yang diujikan. Zona hambat antibakteri menunjukkan adanya zona radikal dan zona irradikal. Ekstrak etanol buah lerak memiliki daya antibakteri yang dapat menghambat pertumbuhan S. epidermidis, S. aureus, dan P. aeruginosa. Sifat dari ekstrak etanol buah lerak terhadap bakteri uji adalah bakteriostatik.Kata kunci: antibakteri; fitokimia; infeksi nosocomial; buah lerak